Implementation of Strategic Policy for the Development of Sustainable Tourism Based on Ecotourism in Kutai Kartanegara Regency - M Ghiffari Ramadhan; Masjaya Masjaya; Bambang Irawan (MASI Mandiri Edukasi, 2026)
This study addresses the problem of suboptimal implementation of Regional Regulation Number 19 of 2016 on the Tourism Development Master Plan in promoting sustainable ecotourism in Samboja and Muara Badak Districts. The objective of this research is to analyze the extent to which the regulation has been implemented and to identify the factors influencing its effectiveness in coastal tourism development. The study applies the Van Meter and Van Horn policy implementation model and Scott’s institutional theory, with emphasis on the regulatory, normative, and cognitive pillars. A qualitative descriptive method was employed. Data were collected through in-depth interviews with officials from the Tourism Office, sub-district governments, destination managers, and Tourism Awareness Groups (Pokdarwis), as well as non-participant observation and documentation review of relevant regulations and planning documents. Data were analyzed using data condensation, data display, and conclusion drawing techniques. The results indicate that the policy has clear objectives, including increasing tourist visits, promoting community empowerment through Pokdarwis, and ensuring environmental sustainability. However, implementation remains suboptimal due to the absence of derivative technical regulations, limited quantity and quality of human resources, fluctuating regional budgets, inadequate infrastructure, political dynamics, low environmental awareness, and geographical challenges such as coastal abrasion and land conflicts. From an institutional perspective, the regulatory, normative, and cognitive pillars are present but require strengthening, particularly to enhance community capacity and ensure policy consistency.